Genetic Survey of Autosomal Recessive Peripheral Neuropathy Cases Unravels High Genetic Heterogeneity in a Turkish Cohort. (31st October 2021) - Candayan, Ayşe; Çakar, Arman; Yunisova, Gulshan; Özdağ Acarlı, Ayşe Nur; Atkinson, Derek; Topaloğlu, Pınar; Durmuş, Hacer; Yapıcı, Zuhal; Jordanova, Albena; Parman, Yeşim; Battaloğlu, Esra
Abstract : Background and Objectives: Inherited peripheral neuropathies (IPNs) are a group of genetic disorders of the peripheral nervous system in which neuropathy is the only or the most predominant clinical feature. The most common type of IPN is Charcot-Marie-Tooth (CMT) disease. Autosomal recessive CMT (ARCMT) is generally more severe than dominant CMT and its genetic basis is poorly understood due to high clinical and genetic diversity. Here, we report clinical and genetic findings from 56 consanguineous Turkish families initially diagnosed with CMT disease. Methods: We initially screened the GDAP1 gene in our cohort as it is the most commonly mutated ARCMT gene. Next, whole-exome sequencing and homozygosity mapping based on whole-exome sequencing (HOMWES) analysis was performed. To understand the molecular impact of candidate causative genes, functional analyses were performed in patient primary fibroblasts. Results: Biallelic recurrent mutations in the GDAP1 gene have been identified in 6 patients. Whole-exome sequencing and HOMWES analysis revealed 16 recurrent and 13 novel disease-causing alleles in known IPN-related genes and 2 novel candidate genes: 1 for a CMT-like disease and 1 for autosomal recessive cerebellar ataxia with axonal neuropathy. We have achieved a potential genetic diagnosis rate of 62.5% (35/56 families) in our cohort. Considering only the variants that meet the American College for Medical Genetics and Genomics (ACMG) classification as pathogenic or likely pathogenic, the definitive diagnosis rate was 55.35% (31/56 families). Discussion: This study paints a genetic landscape of the Turkish ARCMT population and reports additional candidate genes that might help enlighten the mechanism of pathogenesis of the disease.